Markers of Airway Remodeling in Bronchopulmonary Diseases - O.Ye. Chernyshova (Zaslavsky O.Yu., 2014)
The article presents information about markers of airway remodeling in bronchopulmonary diseases. There is described the influence of matrix metalloproteinases, tissue inhibitor of matrix metalloproteinase, transforming growth factor, collagen autoantibodies III type, endothelin-1 on the processes of morphological airway reconstruction as smooth muscle hypertrophy, enhanced neovascularization, epithelial cell hyperplasia, collagen deposition, compaction of the basal membrane, observed in bronchial asthma.